Nuclear Coregulatory Complexes in Tregs as Targets to Promote Anticancer Immune Responses - Christensen, Lanette M.; Hancock, Wayne W. (Frontiers in Immunology, 2022)
T-regulatory (Treg) cells display considerable heterogeneity in their responses to various cancers. The functional differences among this cell type are heavily influenced by multiprotein nuclear complexes that control their gene expression. Many such complexes act mechanistically by altering epigenetic profiles of genes important to Treg function, including the forkhead P3 (Foxp3) transcription factor. Complexes that form with certain members of the histone/protein deacetylase (HDAC) class of enzymes, like HDACs 1, 2, and 3, along with histone methyltransferase complexes, are important in the induction and stabilization of Foxp3 and Treg identity. The functional behavior of both circulating and intratumoral Tregs greatly impacts the antitumor immune response and can be predictive of patient outcome. Thus, targeting these regulatory complexes within Tregs may have therapeutic potential, especially in personalized immunotherapies.